THE WAR AGAINST THE POOR - Hook, Derek (PINS-Psychology in Society, 2025)
Gibson, Nigel, C (2011) Fanonian practices in South Africa. From Steve Biko to Abahlali baseMjondolo. Pietermaritzburg: UKZN Press / New York: Palgrave Macmillan. ISBN 978-1-86914-197-4. Pages xxii + 312. Nigel Gibson claims that without the establishment of the shack dwellers’ movement Abahlali baseMjondolo, he would not have been able to write Fanonian practices in South Africa. This is true, for while the book contains much of considerable theoretical value from one of the world’s foremost Fanon scholars, it is its grounding in the South African context, and particularly, in the struggles of Abahlali, that really underlies the force of the arguments presented.